A comparison between the gastric and salivary concentration of iodide, pertechnetate, and bromide in man. Issue 11 (November 1969) - Harden, R. McG.; Alexander, W. D.; Shimmins, J.; Chisholm, D.
Abstract : The concentration of iodide (I − ) and pertechnetate (TcO4 − ) and bromide (Br − ) has been measured simultaneously in gastric juice and parotid saliva. The combined gastric and salivary clearance for iodide and pertechnetate is more than twice the clearance of these ions by the thyroid gland. The concentration of the ions was in the order I − >TcO4 − >Br − in both gastric juice and saliva. Differences exist between the secretion of iodide, pertechnetate, and bromide. Bromide, in contrast to iodide and pertechnetate, was found to be more concentrated in gastric juice than in saliva. The ratio of the iodide to pertechnetate clearance was greater in gastric juice than in saliva.